Peran Kemandirian Belajar Terhadap Prestasi Belajar Mahasiswa Pada Era New Normal - Eka Kurniawan (Griya Journal of Mathematics Education and Application, 2022)
This study aims to further examine the role of determining the success of learning mathematics education students in the new normal era. The focus of this research is on student learning independence that affects learning achievement. This type of research is ex post facto. The subjects in this study were 100 mathematics education students, at FKIP Mataram University in the seventh semester of the academic year 2021/2022. Data collection uses a learning independence questionnaire, then learning achievement data is taken from the 6th semester IP (achievement index) for the 2020/2021 academic year. Test the significance of the effect of the dependent variables on the independent variables partially. The results showed that the relationship between learning independence and student achievement can be described by the equation Y = 3.318 + 0.027X with a contribution of 18.1% to student achievement. The conclusion of this study is that there is a partial significant effect between independent learning and student achievement in the new normal era.